AKHLAK PENDIDIK DAN PESERTA DIDIK (PRESPEKTIF KH. M. HASYIM ASY’ARI DAN PROF. DR. Hj. ZAKIYAH DARADJAT) - Rusdiyanto, Ali; Hijriyati, Muthi’ah; Arini, Aida (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2020)
National education begins which to put aside the moralvalues that the authors include as the background of this study, it canbe seen from the number of educators and students who experiencea decline or even do not have the value of politeness. Indeed, theformation of morals or character is the main goal in Islamic educationwhich can form a moral, pure, and clean soul and able to distinguishbetween truth and fault. The author's interest is to study how KH.M. Hasyim Asy'ari and Prof. Dr. Hj. Zakiyah Daradjat suggests amoral education that can solve the problem of moral depravity thatoccurs in this country. The aims of this research are 1. To find outhow moral education focuses on the morals of educators andstudents Perspective KH. M. Hasyim Asy'ari and Prof. Dr. Hj.Zakiyah Daradjat, 2. To find out the similarities and differences inthe morals of educators and students from the perspective of KH.M. Hasyim Asy'ari and Prof. Dr. Hj. Zakiyah Daradjat. The libraryresearch is used in this writing. Research with literature reading as thebasis for data collection was carried out carefully so that theinformation was relevant to the research topic or study topic. Also inthis research approach is a qualitative approach, with content analysismethods to analyze its content as well as scientific analysis of thought.The context in this study and focuses on education which focuses onmorals by Kyai Hasyim Asy'ari and Prof. Dr. Hj. Zakiyah Daradjat.The research shows 1. Education that focuses on the moralperspective of KH. M. Hasyim Asy'ari includes 2 aspects, namely: 1) Educators include a. educators who must have morals b. how tobecome a professional educator and his efforts c. an educator'sstrategy in teaching 2) Learners include a. students who prioritizemorals b. efforts to become students with good morals c. strategiesand procedures for students in learning. 2. Prof. perspective moraleducation. Dr. Hj. Zakiyah Daradjat where 3 factors are the main basis, namely: a. factor figure b. texture factor c. cultural factors 3. The similarity of moral education offered by Hasyim and Mrs.Zakiyah, namely in terms of educational materials, which are bothalways reminded to get closer to Allah SWT, moral education(interaction between educators and students), and social relationsbasic namely the community. 4. There are also differences in theformation of KH M. Hasyim Asy'ari who is more inclined towardsthe educational environment because KH. M. Hasyim Asy'ari is inthe pesantren environment, Prof. Dr. Hj. Zakiyah Daradjat is locatedin a family environment.